2013
DOI: 10.1021/jf400440b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Electrospun Poly(lactic acid) (PLA) Nanofibrous Webs Incorporating Triclosan/Cyclodextrin Inclusion Complexes

Abstract: Solid triclosan/cyclodextrin inclusion complexes (TR/CD-IC) were obtained and then incorporated in poly(lactic acid) (PLA) nanofibers via electrospinning. α-CD, β-CD, and γ-CD were tested for the formation of TR/CD-IC by a coprecipitation method; however, the findings indicated that α-CD could not form an inclusion complex with TR, whereas β-CD and γ-CD successfully formed TR/CD-IC crystals, and the molar ratio of TR to CD was found to be 1:1. The structural and thermal characteristics of TR/CD-IC were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
110
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 44 publications
8
110
0
Order By: Relevance
“…Incorporation of QU/b-CD-IC into electrospun nanofibres could be a valuable approach to use QU in a more efficient way, because of the high surface area-tovolume ratio and highly porous structure of nanofibres. Related studies on CD-IC incorporated electrospun nanofibres for different purposes have already been reported by our group (Aytac, Dogan, Tekinay, & Uyar, 2014;Aytac, Sen, Durgun, & Uyar, 2015;Canbolat, Celebioglu, & Uyar, 2014;Celebioglu, Umu, Tekinay, & Uyar, 2014;Kayaci, Ertas, & Uyar, 2013;Kayaci, Sen, Durgun, & Uyar, 2014;Kayaci, Umu, Tekinay, & Uyar, 2013;Kayaci & Uyar, 2012). CDs were also used for crosslinking of polymeric materials (Li & Hsieh, 2005;Liu, Zhang, Liu, Ni, & Li, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Incorporation of QU/b-CD-IC into electrospun nanofibres could be a valuable approach to use QU in a more efficient way, because of the high surface area-tovolume ratio and highly porous structure of nanofibres. Related studies on CD-IC incorporated electrospun nanofibres for different purposes have already been reported by our group (Aytac, Dogan, Tekinay, & Uyar, 2014;Aytac, Sen, Durgun, & Uyar, 2015;Canbolat, Celebioglu, & Uyar, 2014;Celebioglu, Umu, Tekinay, & Uyar, 2014;Kayaci, Ertas, & Uyar, 2013;Kayaci, Sen, Durgun, & Uyar, 2014;Kayaci, Umu, Tekinay, & Uyar, 2013;Kayaci & Uyar, 2012). CDs were also used for crosslinking of polymeric materials (Li & Hsieh, 2005;Liu, Zhang, Liu, Ni, & Li, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…Active agents loaded electrospun nanofibers may be useful in food packaging [3,4,[7][8][9][10][11] and biomedical applications [12][13][14] as reported in the literature. Vega-Lugo et al made comparison in terms of release characteristics of free AITC and AITC/␤-CD-IC including soy protein nanofibers with changing relative humidity and they also studied the effect of AITC amount on the release of AITC from AITC including polylactic acid nanofibers in different relative humidity [8].…”
Section: Introductionmentioning
confidence: 98%
“…[1,2]. Owing to the room temperature and ambient process conditions that provide protection for the bioactive compounds in electrospun nanofibers, electrospinning is used for production of functional nanofibers containing active agents like antioxidants [3,4], flavors/fragrances [5,6] and antibacterial agents [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Figure 6, the typical diffraction peaks for pure PLA at 2θ=16.6, 19.1, 22.5, and 14.9 o were clearly observed while major peaks of β-CD appeared at 6.53, 9.3, 12.7 and 23.1 o , respectively which were consistent with the literatures. 33,34 It can be found that the XRD pattern of β-CD-PLA ICs is totally different from that of PLA and β-CD. Compared with pure PLA, with the content of the added β-CD increasing, the peaks of ICs were dramaticlly weaken and tightened.…”
Section: 폴리머 제39권 제2호 2015년mentioning
confidence: 99%